Simbol-simbol Keagamaan dan Budaya dalam Identitas Kolektif Desa Tunjungrejo melalui Perspektif Sosiologi Budaya - Muhammad Sifa’ Muizzuddin; Septian Bintang Cahyo; Rizqi Ahmad Muzaki; Tegar Vicho Virdyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Tunjungrejo Village is a clear example of how religious and cultural symbols can become the collective identity and existence of a community. This article describes how symbols such as the cross, coconut shoots, rice, cotton and mountains are not only the dominant manifestation of Christianity in the village, but also display the social dynamics and cultural diversity that exist. These symbols not only illustrate history and religious, economic traditions but also depict the values ​​upheld by society, such as tolerance and interfaith coexistence. Even though there is a Muslim minority in the community, the existence of these symbols reflects an effort to maintain collective identity and existence, while remaining open to interaction and integration with other groups in society. So that it can improve the economic level of village residents through the creative economy. Thus, Tunjungrejo Village is an interesting location to research in understanding the complexity of the relationship between cultural symbols, collective identity, and social dynamics in the context of rural communities.